Activating intramolecular singlet exciton fission by altering π-bridge flexibility in perylene diimide trimers for organic solar cells. Issue 33 (12th August 2020) - Carlotti, Benedetta; Madu, Ifeanyi K.; Kim, Hyungjun; Cai, Zhengxu.; Jiang, Hanjie; Muthike, Angelar K.; Yu, Luping; Zimmerman, Paul M.; Goodson, Theodore
Abstract : We show via time resolved spectroscopy that triplet formation proceeds via intersystem crossing in a rigid-bridged perylene diimide trimer and via efficient and fast intramolecular singlet exciton fission in the analogous flexible-bridged trimer. Abstract : In this study, two analogous perylene diimide (PDI) trimers, whose structures show rotatable single bond π-bridge connection (twisted) vs. rigid/fused π-bridge connection (planar), were synthesized and investigated. We show via time resolved spectroscopic measurements how the π-bridge connections in A–π–D–π–A–π–D–π–A multichromophoric PDI systems strongly affect the triplet yield and triplet formation rate. In the planar compound, with stronger intramolecular charge transfer (ICT) character, triplet formation occurs via conventional intersystem crossing. However, clear evidence of efficient and fast intramolecular singlet exciton fission (iSEF) is observed in the twisted trimer compound with weaker ICT character. Multiexciton triplet generation and separation occur in the twisted (flexible-bridged) PDI trimer, where weak coupling among the units is observed as a result of the degenerate double triplet and quintet states, obtained by quantum chemical calculations. The high triplet yield and fast iSEF observed in the twisted compound are due not only to enthalpic viability but also to the significant entropic gain allowed by its trimeric structure. Our results represent a significant step forward in structure–property understanding, and may direct the design of new efficient iSEF materials.